2013
DOI: 10.1093/humrep/des446
|View full text |Cite
|
Sign up to set email alerts
|

miR-196b targets c-myc and Bcl-2 expression, inhibits proliferation and induces apoptosis in endometriotic stromal cells

Abstract: This work was supported in part by Grants-in-Aid for Scientific Research from the Japan Society for the Promotion of Science (no. 20591920 to K.N. and no. 23592407 to H.N.) and The Uehara Memorial Foundation (to K.N.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 40 publications
1
98
1
Order By: Relevance
“…However, Saare et al (2014) found that miR-200b was upregulated in such tissues. In addition, miR-20a plays an important role in the pathogenesis of ovarian endometriosis by suppressing NTN4 (Zhao et al, 2014), miR23a and miR23b are potential biomarkers of ovarian endometriosis (Shen et al, 2013), and miR196b targets c-myc and Bcl-2 expression, inhibiting proliferation and inducing apoptosis in endometriotic stromal cells (Abe et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, Saare et al (2014) found that miR-200b was upregulated in such tissues. In addition, miR-20a plays an important role in the pathogenesis of ovarian endometriosis by suppressing NTN4 (Zhao et al, 2014), miR23a and miR23b are potential biomarkers of ovarian endometriosis (Shen et al, 2013), and miR196b targets c-myc and Bcl-2 expression, inhibiting proliferation and inducing apoptosis in endometriotic stromal cells (Abe et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence and development of endometriosis may be based on these aberrations in molecular processes, and may be caused by as yet unknown triggers, including miRNA, which initiate these molecular alterations. Certain studies have investigated the role of miRNA expression dysregulation, histone modification and DNA methylation in endometriotic cells (17). Aberrant gene expression associated with epigenetic mechanisms may induce differentiation and the subsequent appearance of an endometriotic phenotype in healthy endometrial cells (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Abe and colleagues (2013) examined the miRNA profiles in endometriotic versus eutopic endometrial stromal cells. Stromal cells were isolated from ovarian endometriomas, while endometrial stromal cells were obtained from eutopic endometrium of women with leiomyomas but no visible signs of endometriosis.…”
Section: 3 Mirnas In Endometrial Physiology and Pathologymentioning
confidence: 99%
“…Right table summarizes miRNAs and their predicted transcript/protein in endometriotic tissue (indicated as red ectopic tissue in the figure) derived from studies incorporating human cells which have been validated. Superscripts refer to references with a = Petracco et al 2011; b = Hawkins et al 2011; c = Abe et al 2013; d = Dai et al 2012; e = Shen et al 2013; f = Adammek et al 2013. Validation refers to either assessing cellular events and/or mRNA and protein levels by modulation of endogenous miRNA levels…”
Section: Fig 91mentioning
confidence: 99%